2022
DOI: 10.1002/hep4.2049
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic retinoic acid receptor alpha mediates all‐trans retinoic acid's effect on diet‐induced hepatosteatosis

Abstract: All-trans retinoic acid (AtRA) is an active metabolite of vitamin A that influences many biological processes in development, differentiation, and metabolism. AtRA functions through activation of retinoid acid receptors (RARs).AtRA is shown to ameliorate hepatic steatosis, but the underlying mechanism is not well understood. In this study, we investigated the role of hepatocyte RAR alpha (RARα) in mediating the effect of AtRA on hepatosteatosis in mice. Hepatocyte-specific Rarα −/− (L-Rarα −/− ) mice and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We showed that g.4478C>G in the upstream region of CD36 is significantly associated with chicken skin yellowness. Further transcription factor prediction showed that CC genotype in this SNP position has more RAR transcription factor binding sites than the GG genotype, and RAR has been reported to regulate CD36 expression ( Zhao et al, 2022 ) and affect fatty acid uptake ( Cassim Bawa et al, 2022 ). The results of dual fluorescein reporter assays in this study further suggested that the CC genotype has higher transcriptional activity than the GG genotype.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that g.4478C>G in the upstream region of CD36 is significantly associated with chicken skin yellowness. Further transcription factor prediction showed that CC genotype in this SNP position has more RAR transcription factor binding sites than the GG genotype, and RAR has been reported to regulate CD36 expression ( Zhao et al, 2022 ) and affect fatty acid uptake ( Cassim Bawa et al, 2022 ). The results of dual fluorescein reporter assays in this study further suggested that the CC genotype has higher transcriptional activity than the GG genotype.…”
Section: Discussionmentioning
confidence: 99%
“…The influx of FFAs from adipose tissue, together with systemic low‐grade inflammation and increased hepatic DNL likely due to delayed glucose clearance, may cause lipotoxicity, ROS production, and apoptosis in the liver of Rarα Adi−/− mice, leading to the development and progression of NAFLD. We have previously shown that loss of RARα in hepatocytes induces hepatosteatosis via inhibiting lipid droplet formation and inducing fatty acid uptake [29]. Thus, adipocyte RARα and hepatocyte RARα regulate the development of hepatosteatosis via distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…To determine intestinal fat absorption, mice were fasted for 6 h and then i.v. injected with tyloxapol (500 μg/kg) prior to gavage with olive oil (15 μl/g body weight) as described ( 19 , 22 ). Plasma TG levels were determined at indicated time points.…”
Section: Methodsmentioning
confidence: 99%